A circular economy use of waste wood sawdust for wood plastic composite production: effect of bio-plasticiser on the toughness. Issue 5 (2nd September 2020) - Petchwattana, Nawadon; Naknaen, Phisut; Narupai, Borwon
ABSTRACT: This research aims to improve the toughness of Poly(lactic acid) (PLA)/wood sawdust (WS) composite by plasticising with tributyrin bio-plasticiser. Experimental results showed the toughness achievement of the plasticised PLA/WS composite, which reflected as the increase of the tensile strain at break and impact resistance. Thermal test indicated that the plasticised composites crystallised earlier than neat PLA and PLA/WS at lower crystallisation temperature (Tc ) together with the increased degree of crystallinity (Xc ). Thermal degradation test revealed that PLA/WS composite were less stable with the plasticiser incorporation, while the heat distortion temperature (HDT) was found to reduce from more than 85°C, in PLA/WS composite, down to less than 60°C when tributyrin was added at 15 wt%. Dynamic mechanical analysis (DMA) indicated that with increasing the tributyrin plasticiser content, the storage modulus (E') was proportionally decreased. Thermogravimetric analysis (TGA) showed that the plasticised PLA/WS composite decomposed earlier than neat PLA and PLA/WS composite due to the decomposition of low molecular weight compositions. Fourier transform infrared (FT-IR) analysis indicated there was no chemical interaction among the raw materials added. The plasticised composites were found to absorb lower amount of water due to the incorporation of non-polar plasticiser.